Effect Combination of Catharanthus roseus and Phyllanthus urinaria Extract on Mice BALB/c Breast Cancer Models Based on T-regulator Cells Expression: T-regulator cells expression on mice BALB/c breast cancer model - Aya shofiyah; M. Sasmito Djati; Muhaimin Rifa'i (Journal of Tropical Life Science, 2022)
CD4+CD25+FOXP3+ is a regulatory T cell that plays a role in the body's tolerant system to control activated effector cells. T regulatory plays an important role as a trigger for tumor progressiveness, where an increase in the amount of T regulatory FOXP3 in the tumor state correlates with a poor prognosis. Breast cancer is a type of cancer that tends to increase every year. The purpose of this study was to study the influence of a combination of Phyllanthus urinaria and Catharanthus roseus plant extracts on CD4+CD25+FOXP3+ modulation. Mice was injected subcutaneously with the carcinogen compound DMBA for six weeks at 0.015 mg/kg weight. The study design was conducted using a complete random design (RAL) which was divided into six groups namely healthy (normal) control, cancer control (DMBA injection), Cisplatin and a combination of extracts with three different doses (dose 1 (Phyllanthus urinaria 500 weight and Catharanthus roseus 75mg/kg weight) and dose 3 (Phyllanthus urinary 2000mg/kg weight and Catharanthus roseus 375mg/kg weight). The relative number of T regulatory cells is measured using flow cytometry analysis. The measurements were made using the Cell Quest ProTM program. Statistics analyze using one way ANOVA (p<0.05). Tukey HSD analysis with SPSS 26 software used to analyze real differences between treatments. A relative increase in CD4+CD25+FOXP3+ occurs in cancer control. While the decrease occurred in every treatment except in the dose group 1. The optimal dose to reduce CD4+CD25+FOXP3+ amounts significantly occurred in the dose group 3. This indicates the influence of a combination of Phyllanthus urinaria and Catharanthus roseus on CD4+CD25+FOXP3+ differentiation. Keywords: breast cancer, Catharanthus roseus, CD4+CD25+FOXP3+, Phyllanthus urinaria,